Pengaruh Model Project Based Learning (PjBL) berbantuan Media Audiovisual terhadap Keterampilan Menulis Teks Cerpen - Anggraini, Fitri; Anggraini, Dewi (Universitas Muhammadiyah Magelang, 2026)
The purpose of this study is to describe the level of short story writing skills of class XI Students of SMK Negeri 1 Timpeh before and after using the Project Based Learning (PjBL) model assisted by audiovisual media on the short story writing skills of class XI students of SMK Negeri 1 Timpeh. The method used in study is one-group pretest-posttest with purposive sampling technique. The sample used in this study is in the form of scores converted into values based on two tests of host story writing skills on the sample. The results of this study are of follows. The short story writing skills of class XI students of SMK Negeri 1 Timpeh before and after using the Project Based Learning (PjBL) model assisted by audiovisual media obtained and average of 59,47 with a Sufficient (C) qualification and 90,00 in Very Good (BS) qualification. The result of this study indicated that there is an influence of the Project Based Learning (PjBL) model assisted by audiovisual media on short story writing skills. This can be seen from the ttest>ttabel value (8,84>2.101) at a significance level of 0,05 and confidence level of 95%.